Spatial and temporal distribution of hailstorms in the Alpine region: a long‐term, high resolution, radar‐based analysis. (30th March 2016) - Nisi, L.; Martius, O.; Hering, A.; Kunz, M.; Germann, U.
Abstract : This article presents a 13‐year hail climatology for Switzerland based on volumetric radar reflectivity. Two radar‐based hail detection products that are used operationally at MeteoSwiss, namely the Probability of Hail (POH) and the Maximum Expected Severe Hail Size (MESHS), have been reprocessed for the extended convective season (April–September) between 2002 and 2014. The result of these two products is a comprehensive hail distribution map, which highlights regional and local‐scale hail characteristics. The map of the annual number of hail days shows a high spatial variability and several maxima over the foothills north and south of the Alps as wells as over the Jura mountains. Directly over the Alps hail frequency exhibits a minimum. Annual hail anomalies show a pronounced variability, which suggests that hail occurrence is strongly controlled by large‐scale weather patterns. Furthermore, hail probability exhibits a strong seasonal and diurnal cycle with a maximum in July in the late afternoon. The hail peak over the northern pre‐alpine region occurs approximately two hours earlier compared to the south. A possible explanation is the trigger mechanism between the cold pool initiated by early convective cells over the Jura mountains and the development of cells on the northern slope of the Alps. Since radar‐based hail signals are only indirect measurements, statistical verification of the hail detection algorithms is crucial. Damage reports from an automobile insurance company are used as an independent dataset. Verification results confirm that radar‐based hail algorithms provide valuable information on hail probability. Finally, the synoptic‐scale hail‐driving weather conditions are investigated using a weather type classification based on upper‐air flow direction and mean pressure from a numerical weather prediction model. The results show that six out of nine main synoptic‐scale patterns favour the development of hailstorms in Switzerland. Abstract : "Analysing hailstorms occurrence over the alpine region through radar based approaches (photo courtesy of Fosco Spinedi and Urs Germann). Two radar based hail detection algorithms have been reprocessed over 13 years providing high spatial and temporal information about hail occurrence over an area with very complex orography like the Alps. Challenges in using radar based approaches on mountainous areas are discussed in detail."